STRATEGIC FORESIGHT AND ITS IMPACT ON SOME PERSPECTIVES OF THE BALANCED SCORECARD FOR THE OPINIONS OF A SAMPLE OF WORKERS IN THE DIYALA MUNICIPALITIES DIRECTORATE - Researcher: Raed Yousef Ali Ahmed; Assist. Prof. Amer Rashid Anied (Scholars Digest Publishing, 2024)
The research aims to identify what is the relationship between strategic foresight in some balanced scorecard perspectives and what is the effect of the independent variable in these perspectives on the dependent variable through the dimensions associated with each variable, represented by the dimensions of strategic foresight (environmental surveyability, strategic choice, integration capability, and future vision) and the perspectives The main and updated balanced scorecard (customer perspective, internal operations, learning and growth perspective, and social and environmental perspective). The Diyala Municipalities Directorate was represented as the research community The sample included all workers in this directorate at their various administrative levels and titles, numbering ( 137 ). The questionnaire was used as a tool for collecting information. The researcher used the descriptive analytical method and used the program ( SPSS - AMOS ) to analyze the data and confirm the validity of the hypotheses. The most important results of the research are the presence of a correlation relationship and a positive moral effect between variables. Search.